PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL STUDIES OF THE LEAF EXTRACT OF COMBRETUM LAMPROCARPUM DIELS (COMBRETACEAE) (FUDMA JOURNAL OF SCIENCES, 2020)
The aim of this study was to determine the antibacterial activity of Combretum lamprocarpum leaf extracts on some clinically isolated bacteria species. The pulverized plant material was extracted by microwave-assisted extraction using chloroform, ethyl acetate and methanol. The Agar well diffusion methods was used to determine the antibacterial activity of the plant against Salmonella typhi, Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli. The phytochemical screening of the extracts revealed the presence of steroids, terpenes, alkaloids, carbohydrates, saponins, tannins, cardiac glycosides and flavonoids. The antibacterial screening of the extracts showed that all the fractions had significant activity against test organisms. The diameter of the zone of inhibition ranged between 14 and 29 mm, the minimum inhibitory concentration ranges between 3.13 and 50.00 mg/mL. The minimum bactericidal concentration was between 6.25 and 50.00 mg/mL. This study revealed that the leaves of Combretum lamprocarpum has a medicinal value in treating bacterial infections.
Keywords: Combretum lamprocarpum, Combretaceae, leaf extract, microwave-assisted extraction